Súditos e protestantes: o impacto da propaganda protestante no sistema jurídico do Brasil Império (1835-1889). - Silva, Edjaelson Pedro da (2021)
The insertion of Protestantism in Brazil, in the 19th century, demanded, on the part of the missionaries, the creation of strategies that aimed at a greater reach of evangelization, the strengthening and the permanence of the results obtained. Early on, the question of the legal order was perceived as one of the battlefields to be conquered. In the Brazilian order of the day, there was no provision that a national could be non-Catholic, with the entire building of civil rights being structured based on this premise. With non-Catholic baptism in Brazil, a fact is founded that missionaries seek to value and lead to the creation of a norm to assimilate the Protestant element. Analyzing newspapers, letters, denominational stories, books of the time and text of law, in comparison with the theses of cultural history, with an analysis of the religious field from the perspective of Pierre Bourdieu and Miguel Realle's Three-dimensional Theory of Law, this research has as thesis that the struggle for the protestant insertion in Brazil ended up provoking a positive change in the legal diplomas in matter of Civil Law still in Brazil Empire.